Stereological Study on the Positive Effect of Running Exercise on the Capillaries in the Hippocampus in a Depression Model - Chen, Linmu; Zhou, Chunni; Tan, Chuanxue; Wang, Feifei; Gao, Yuan; Huang, Chunxia; Zhang, Yi; Jiang, Lin; Tang, Yong (Frontiers in Neuroanatomy, 2017)
Running exercise is an effective method to improve depressive symptoms when combined with drugs. However, the underlying mechanisms are not fully clear. Cerebral blood flow perfusion in depressed patients is significantly lower in the hippocampus. Physical activity can achieve cerebrovascular benefits. The purpose of this study was to evaluate the impacts of running exercise on capillaries in the hippocampal CA1 and DG regions. The chronic unpredictable stress (CUS) depression model was used in this study. CUS rats were given four weeks of running exercise from the fifth week to the eighth week (20 minutes every day from Monday to Friday each week). The sucrose consumption test was used to measure anhedonia. Furthermore, stereological methods were used to investigate the capillary changes among the control group, CUS/Standard group and CUS/Running group. Sucrose consumption significantly increased in the CUS/Running group. Running exercise has positive effects on the capillaries parameters in the hippocampal CA1 and DG regions, such as the total volume, total length and total surface area. These results demonstrated that capillaries are protected by running exercise in the hippocampal CA1 and DG might be one of the structural bases for the exercise-induced treatment of depression-like behavior. These results suggest that drugs and behavior influence capillaries and may be considered as a new means for depression treatment in the future.